EXPLORING COHESIVE DEVICES USED BY STUDENTS IN NARRATIVE TEXT - Aulia, Nabila; Nugraha, Sidik Indra; Miftakh, Fauzi (Peneliti.net, 2024)
Finding out the different kinds of cohesive devices and how frequently they occur is the goal of this study. The research used qualitative research as a research design. The participants of the study are 6 students in of the senior high school in Karawang who are selected based on the recommendation of the English teacher to collect data. The instruments used in this study were document analysis. The data were then analyzed in accordance to Halliday and Hasan (1976) which cater grammatical cohesion (reference, substitution, ellipsis, conjunction), and lexical cohesion (reiteration and collocation). The researcher discovered that lexical cohesiveness is subordinated to grammatical cohesion. Ellipsis and collocation are the only two aspects of the four that belong to grammatical coherence and the two that belong to lexical cohesion that are absent from the students' narrative texts. With 39 appearances, conjunction is a dominant word in student narrative texts. While the reference in the second position requires 20 appearances, the replacement plays the final three appearances. Conversely, lexical cohesiveness makes a total of six occasions. The most common appearances are repetitions, with six and There are no collocations in the pupils' narrative text.